Can Agropolitan Promise Prosperity and Sustainability? - Alfian Rosiadi; Oky Juniarko; Pera Wibowo Putro; Dian Surya Ayu Fatmawati (The Journal of Indonesia Sustainable Development Planning, 2022)
This paper aims to formulate development strategies for agribusiness and agroindustry areas in Kawasan Agropolitan Sendang (KAS) as a development priority area in Tulungagung. It provided alternative KAS development strategies to overcome some obstacles over the last 16 years. Since KAS is one of the national priority development objects, further studies are required to determine the best development planning formulation. The methodology used in this research is a case study method with three analyses, policy analysis, analysis of environmental conditions, and SWOT analysis. The results show that KAS needs to develop the hinterlands and cooperate in providing infrastructures such as banking institutions, markets, and road networks. Farmer groups need to participate in empowerment programs on skill training and improving the quality of innovative and creative agropolitan product standardization and counseling on socio-economic fluctuations that impact people's lifestyles and behavior.